Ethics-Based Professionalism of Notaries and PPAT: The Main Pillar In Carrying Out Professional Duties - Agung Iriantoro (PT. Global Research Collaboration, 2026)
Notaries and Land Deed Officials (PPAT) are public officials authorized by the state to produce authentic deeds with strong evidentiary value in civil and land law systems. This authority is accompanied by a high level of public trust, requiring not only legal compliance but also strong ethical responsibility. This study aims to analyze the professionalism of Notaries and PPAT as state-trusted public officials and to examine how professional ethics function as a fundamental mechanism in strengthening accountability and legal certainty in their practice. The research employs normative legal research with statutory and conceptual approaches, supported by literature review of laws, regulations, ethical codes, and scholarly writings. This study does not use a case-study approach. The study finds that professionalism of Notaries and PPAT is structured through an integrated framework consisting of statutory authority, ethical codes, and supervisory mechanisms. However, a gap remains between normative ethical standards and their practical implementation, particularly in issues related to conflicts of interest, indirect promotion, and neutrality in practice. This study proposes an integrative framework of ethics-based professionalism that positions professional ethics not as a complementary element, but as a binding foundation ensuring legal certainty, institutional accountability, and public trust in the execution of authentic deed services.